PEMBERDAYAAN WANITA DALAM UPAYA MENINGKATKAN EKONOMI RUMAH TANGGA - Iin Wijayanti (BAJ: Behavioral Accounting Journal, 2020)
This study was designed to describe the economic situation of rural households that focus on agricultural land and the role of women in Pangkal Village, Sawoo District. This study uses qualitative data analysis activities carried out in the field and even in conjunction with the process of data conversion in in-depth interviews, data reduction. Conclusions are drawn if the data collected is considered sufficient and considered complete. The number of samples taken from land bag farmers consisted of women who directly worked on the land bags themselves. The results of this study illustrate the economy in Pangkal Village, Sawoo District, with the contribution of land use in Tasen which greatly helps improve the economy of the community, involving the participating government, by providing seed subsidies, fertilizer and rental freedom from the Department of Forestry, so that the community can benefit. In this case the role of women is a double workload. They are able to hoe, irrigate plants, weed grass, provide fertilizer, care for plants, harvest crops and sell them. For them "work as a choice" for the fulfillment of family life needs.